Legalitas Transaksi Jual Beli Sepeda Motor Tanpa Bukti Kepemilikan dalam Perspektif Sadd Al-Żarī‘Ah - Eriyanti, Nahara; Sarami, Ayu (Sharia Faculty Islamic Economic Law Study Department, 2020)
This study is aimed to find out how the legal status of buying and selling motorbikes without vehicle registration STNK and BPKB, where many of the people of the District of Kebharga, especially Kala Lengkio Village and Mendale Village, conduct transactions of buying and selling motorbikes without STNK and BPKB. In general, buying and selling carried out by the public has fulfilled the legal requirements of buying and selling in Islam, which does not explain in detail that buying and selling motorbikes without the STNK of BPKB is a sale and purchase which is canceled. Unlike the case with the police which states that buying and selling motorbikes without a STNK and BPKB is a canceled sale. Based on the description above that is the focus of research on the formulation of the problem namely: how to buy and sell motorbikes without proof of ownership in the community of the District of Kebayakan and how is its legality from the perspective of sadd al-‘arī‘ah ?. In this study the author uses the case study research method then analyzed using the theory of sadd al-‘arī‘ah, then in the technique of collecting data the author uses interviews / interviews. The results of the study that the authors get about buying and selling motorbike transactions without proof of ownership and analyzed using the theory of sadd al-īarī'ah that looks at the benefits and mafsadat arising, then the motorcycle sale and purchase transactions without proof of ownership there is a level of understanding that is superior to with benefit, the sale and purchase of the people of the district is a sale that must be prevented and must also be avoided by the community because the sale can cause a lot of damage even though the sale of a motorcycle is a sale that is in accordance with the terms and conditions of the legal sale.